Preparing a dual-function BiVO4/NiFe-LDH composite photoanode for enhanced photoelectrocatalytic wastewater treatment and simultaneous hydrogen evolution. (25th July 2022) - Cong, Sumin; Yu, Jiuheng; Liu, Baojun; Teng, Wei; Tang, Yubin
Abstract : The proposed PEC degradation over the BiVO4 /NiFe-LDH photoelectrode under visible light irradiation and simultaneous hydrogen evolution at the cathode. Abstract : BiVO4 /NiFe was synthesized on Ni foam using a simple hydrothermal method and successive ion layer absorption and reaction (SILAR) method. The BiVO4 /NiFe electrode was used as a photoanode for photoelectrocatalytic (PEC) degradation of tetracycline (TC) in wastewater with simultaneous cathodic hydrogen production. The photoelectrochemical and catalytic properties of the prepared electrodes were studied using a series of characterization and measurements. The unique Z-scheme BiVO4 /NiFe heterojunction has a synergistic effect, which can significantly improve the absorption of visible light, accelerate the charge transfer and consequently inhibit the complexation of e − –h + pairs. These characteristics of the heterojunction contribute to the prominent PEC performance of the BiVO4 /NiFe electrode. The trapping experiment showed that holes (h + ) are the main active substances in the degradation process, and the electrode has good cyclic stability that the degradation efficiency had not decayed significantly after five repeated experiments. In addition, the BiVO4 /NiFe photoanode displayed favorable degradation and cathodic hydrogen evolution efficiency simultaneously in the real sunlight conditions. This study provides a basis for the design of highly practical photoelectric electrodes and expands the application of PEC technology.